Ten years of positive feedback on project-based learning from first-year engineering students’ perspective - Alves, Anabela Carvalho (2020)
Project-Based Learning (PBL) is an active student-centered learning methodology. Several schools (of varying degrees of education) have implemented, in different ways, PBL, having as common strands that the student learns in teams, and being challenged in the context of a case-scenario. In Portugal, a PBL methodology has been implemented, in the first year of an Industrial Engineering and Management (IEM) program, for more than 15 years. This represents a total number above 700 students of IEM enrolled in PBL during the reported timeframe. A continuous improvement process of the PBL activities was relentlessly pursued during such period. Grounded on end-ofterm on-line PBL process satisfaction questionnaires, as well as on results of each PBL edition final workshops, this paper studies and reports on a number of such achievements and shortcomings. Thus, this paper presents the analysis of the results of ten academic years of PBL evaluation process, grounded on the compiled results obtained from 2009/10 to 2019/20. Also, a synthesis of the effective findings (either positive or negative), systematically pointed out by the students, will be presented. Altogether, the PBL implementation in the IEM program has been very positive for students and teachers and worth for others to follow.